APPsα rescues impaired Ca2+ homeostasis in APP- and APLP2-deficient hippocampal neurons - Ludewig, Susann; Herrmann, Ulrike; Michaelsen-Preusse, Kristin; Metzdorf, Kristin; Just, Jennifer; Bold, Charlotte; Müller, Ulrike C.; Korte, Martin (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Alterations in Ca2+ homeostasis have been reported in several in vitro and in vivo studies using mice expressing the Alzheimer’s disease-associated transgenes, presenilin and the amyloid precursor protein (APP). While intense research focused on amyloid-β-mediated functions on neuronal Ca2+ handling, the physiological role of APP and its close homolog APLP2 is still not fully clarified. We now elucidate a mechanism to show how APP and its homolog APLP2 control neuronal Ca2+ handling and identify especially the ectodomain APPsα as an essential regulator of Ca2+ homeostasis. Importantly, we demonstrate that the loss of APP and APLP2, but not APLP2 alone, impairs Ca2+ handling, the refill of the endoplasmic reticulum Ca2+ stores, and synaptic plasticity due to altered function and expression of the SERCA-ATPase and expression of store-operated Ca2+ channel-associated proteins Stim1 and Stim2. Long-term AAV-mediated expression of APPsα, but not acute application of the recombinant protein, restored physiological Ca2+ homeostasis and synaptic plasticity in APP/APLP2 cDKO cultures. Overall, our analysis reveals an essential role of the APP family and especially of the ectodomain APPsα in Ca2+ homeostasis, thereby highlighting its therapeutic potential.
Im Text ist "2+" hochgestellt
Gesehen am 19.08.2021